2019
DOI: 10.1089/aivt.2019.0008
|View full text |Cite
|
Sign up to set email alerts
|

Functional Comparison of HepaRG Cells and Primary Human Hepatocytes in Sandwich and Spheroid Culture as Repeated-Exposure Models for Hepatotoxicity

Abstract: Introduction: Reliable and effective predictions of hepatotoxicity resulting from repeated exposure to chemicals are of critical importance for the safety assessment of chemicals; however, in vitro long-term repeated-exposure studies are difficult to conduct using conventional hepatocyte monolayer cultures due to de-differentiation and subsequent loss of hepatocyte function. Alternative in vitro culture techniques have emerged to address this challenge and have improved the longevity of hepatocyte cultures. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Conventionally, this has involved culturing primary human hepatocytes or immortalized/cancer-derived cell lines as 2D monolayers. However, the cells used in these models will often be phenotypically different from in-vivo hepatocytes (i.e., Ammonia metabolism/urea secretion is higher in spheroids (73) Gene expression is higher and/or maintained for longer for a number of phase I proteins in spheroid cultures (68,141,144) Activity for CYP450 enzymes involved in xenobiotic metabolism is higher and /or maintained for longer in spheroids (71,73,89,141) Protein expression for a number of phase I, II, and III proteins is maintained for longer in spheroids (71) CYP1A2, 2C9, 2C19, and 3A4 more inducible to known pharmacological inducers (89) Gene expression for phase II and III proteins, nuclear receptors, and hepatocyte markers is higher and/or maintained for longer in spheroids (141,144) GSTP1 gene expression lower in spheroids (141) CYP4A11 and SLC27A5 expression lost more rapidly in spheroids (71) Lower protein expression for some basolateral transporters in spheroids (71) Proteomic and metabolite profile is more stable in 3D cultures over time (71,141) Spheroid cultures have greater sensitivity to detect toxicity for known hepatotoxic compounds at toxicologically relevant concentrations (71,73,81) Spheroid cultures show greater recovery from the dedifferentiation process associated with in-vitro culture, when considering gene expression (74) cancer-derived cell lines), or rapidly dedifferentiate, becoming metabolically incompetent, when cultured in vitro (i.e., PHH). This hinders their ability to investigate metabolism-dependent toxicities and limits their application for detecting DILI-positive compounds, particularly over chronic and repeat dose time courses that are more emulative of in-vivo manifestations of DILI.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…Conventionally, this has involved culturing primary human hepatocytes or immortalized/cancer-derived cell lines as 2D monolayers. However, the cells used in these models will often be phenotypically different from in-vivo hepatocytes (i.e., Ammonia metabolism/urea secretion is higher in spheroids (73) Gene expression is higher and/or maintained for longer for a number of phase I proteins in spheroid cultures (68,141,144) Activity for CYP450 enzymes involved in xenobiotic metabolism is higher and /or maintained for longer in spheroids (71,73,89,141) Protein expression for a number of phase I, II, and III proteins is maintained for longer in spheroids (71) CYP1A2, 2C9, 2C19, and 3A4 more inducible to known pharmacological inducers (89) Gene expression for phase II and III proteins, nuclear receptors, and hepatocyte markers is higher and/or maintained for longer in spheroids (141,144) GSTP1 gene expression lower in spheroids (141) CYP4A11 and SLC27A5 expression lost more rapidly in spheroids (71) Lower protein expression for some basolateral transporters in spheroids (71) Proteomic and metabolite profile is more stable in 3D cultures over time (71,141) Spheroid cultures have greater sensitivity to detect toxicity for known hepatotoxic compounds at toxicologically relevant concentrations (71,73,81) Spheroid cultures show greater recovery from the dedifferentiation process associated with in-vitro culture, when considering gene expression (74) cancer-derived cell lines), or rapidly dedifferentiate, becoming metabolically incompetent, when cultured in vitro (i.e., PHH). This hinders their ability to investigate metabolism-dependent toxicities and limits their application for detecting DILI-positive compounds, particularly over chronic and repeat dose time courses that are more emulative of in-vivo manifestations of DILI.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Comparable activity was seen for CYP1A2 with 2D monolayers and 3D spheroids ( 70 , 73 ), although another study reported significantly higher CYP1A activity (i.e., using EROD assay) ( 119 ). CYP2B6 activity was shown to be higher for 3D spheroids ( 70 , 73 ). HepaRG spheroids display inducible CYP450 enzymes in response to known pharmacological inducers, indicating functional nuclear receptors (i.e., PXR, CAR, and AhR) ( 70 , 88 , 104 , 119 ).…”
Section: Immortalized/cancer Cell Linesmentioning
confidence: 98%
See 2 more Smart Citations
“…In the present study, we used human HepaRG hepatocytes due to their metabolic competence to evaluate the appropriateness of 3D constructs for toxicity testing. Our 3D constructs exhibited long-term stability and cell viability, which is suitable for chronic toxicity testing in vitro similar to the 3D organoids and spheroids [ 33 ]. It has been shown that AFB1 treatment induces cell toxicity and loss of metabolic activity of HepaRG spheroid model ([ 34 ], [ 35 ]).…”
Section: Discussionmentioning
confidence: 99%